2019
DOI: 10.1103/physrevd.99.125011
|View full text |Cite
|
Sign up to set email alerts
|

Extensivity, entropy current, area law, and Unruh effect

Abstract: We present a general method to determine the entropy current of relativistic matter at local thermodynamic equilibrium in quantum statistical mechanics. Provided that the local equilibrium operator is bounded from below and its lowest lying eigenvector is non-degenerate, it is proved that, in general, the logarithm of the partition function is extensive, meaning that it can be expressed as the integral over a 3D space-like hypersurface of a vector current, and that an entropy current exists. We work out a spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…where, as before, we assume a = √ −a µ a µ , and ρ 0 , p 0 , A 1 , A 2 , A 3 , A 4 , B 1 , B 2 are coefficients to be defined. The formula (2.2) is the most general expression allowed by parity requirements in the fourth order of perturbation theory (look [13]). In [16] coefficients up to the second order of the perturbation theory were calculated.…”
Section: Unruh Effect From Density Operatormentioning
confidence: 99%
See 4 more Smart Citations
“…where, as before, we assume a = √ −a µ a µ , and ρ 0 , p 0 , A 1 , A 2 , A 3 , A 4 , B 1 , B 2 are coefficients to be defined. The formula (2.2) is the most general expression allowed by parity requirements in the fourth order of perturbation theory (look [13]). In [16] coefficients up to the second order of the perturbation theory were calculated.…”
Section: Unruh Effect From Density Operatormentioning
confidence: 99%
“…In [8,9] it was shown that the hadronization process can be accompanied by accelerated particle motion, which can be a source of thermalization in elementary processes such as e + e − annihilation or pp and pp collisions, just due to the Unruh effect, and also allows to explain some features in the multiplicities of hadrons. So in the elementary processes of electron-positron annihilation or proton-(anti)proton collisions, tremendous accelerations can occur, which may open the way for observing the effects associated with acceleration, while in heavy ion collision also large vorticity may arise, and polarisation in heavy ion collisions provides information both about vorticity and acceleration [10,11].An interesting new look at the Unruh effect was recently obtained from the standpoint of quantum relativistic statistical mechanics [12,13]. In [12] it was shown by calculating the values of quantum correlators for scalar fields at a finite temperature that the average value of any local operator turns out to be zero after subtracting of the vacuum contribution at the proper temperature, measured by a comoving observer, equal to the Unruh temperature.…”
mentioning
confidence: 99%
See 3 more Smart Citations